Kegiatan Pengabdian Masyarakat dengan Pemeriksaan Awal Parameter Sindrom Metabolik (Gula Darah Puasa, Trigliserida, Lingkar Perut, HDL dan Tekanan Darah) pada Kelompok Usia Produktif di SMA Kalam Kudus II - Ernawati Ernawati; Alexander Halim Santoso; Ayleen Nathalie Jap; Bryan Anna Wijaya; Fiona Valencia Setiawan; Stanislas Kotska Marvel Mayello Teguh; Edwin Destra; Farell Christian Gunaidi (jurnal ABDIMAS Indonesia, 2025)
Metabolic syndrome is a cluster of conditions that increases the risk of cardiovascular diseases and type 2 diabetes mellitus. Early screening of metabolic parameters such as fasting blood glucose, triglycerides, waist circumference, HDL cholesterol, and blood pressure is essential for risk detection and prevention of complications. This community service activity was conducted at SMA Kalam Kudus II, involving education on metabolic syndrome and screening of metabolic parameters in the productive age group. The education aimed to raise awareness of healthy lifestyles and the importance of routine screening. Early detection enables preventive actions and lifestyle improvements, such as balanced diets, regular exercise, and stress management. The program's implications include long-term reductions in metabolic disease risks. Education and metabolic syndrome screening have proven effective in raising awareness of metabolic health.